1998
DOI: 10.1016/s0378-1097(98)00186-4
|View full text |Cite
|
Sign up to set email alerts
|

Properties and sequence of the coenzyme B12-dependent glycerol dehydratase of Clostridium pasteurianum

Abstract: The genes encoding coenzyme B IP -dependent glycerol dehydratase of Clostridium pasteurianum were subcloned and expressed in Escherichia coli. The native molecular mass of the enzyme is 190 000 Da. The enzyme converts glycerol, 1,2-propanediol and 1,2-ethanediol to 3-hydroxypropionaldehyde, propionaldehyde and acetaldehyde, respectively, but glycerol is the preferred substrate. The nucleotide sequences of the dhaBCE genes encoding the three subunits of glycerol dehydratase and of orfZ whose function is unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 18 publications
4
54
0
6
Order By: Relevance
“…To cover the different annealing temperatures of the degenerated primer pair, 10 PCRs per sample were performed in a gradient cycler. For calibration of the PCRs, the genes encoding the dehydratases of C. freundii (41) and Clostridium pasteurianum (28,29) were used as positive controls. The reactions were performed by using the isolated recombinant plasmids pMS2 and pFL1, respectively, as sources for the dehydratase genes of these organisms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To cover the different annealing temperatures of the degenerated primer pair, 10 PCRs per sample were performed in a gradient cycler. For calibration of the PCRs, the genes encoding the dehydratases of C. freundii (41) and Clostridium pasteurianum (28,29) were used as positive controls. The reactions were performed by using the isolated recombinant plasmids pMS2 and pFL1, respectively, as sources for the dehydratase genes of these organisms.…”
Section: Methodsmentioning
confidence: 99%
“…Conserved regions of coenzyme B 12 -dependent glycerol dehydratases (GDHs) and diol dehydratases (DDHs) selected for generation of degenerate oligonucleotides. Sequences from C. freundii (41); Clostridium pasteurianum (29); K. pneumoniae (44); K. oxytoca (45); and S. enterica serovar Typhimurium (6) are shown.…”
Section: Methodsmentioning
confidence: 99%
“…The reason is that the gene for the subunit B of the coenzyme B 12 -dependent glycerol dehydratase complex is missing. In this respect it is of interest that glycerol dehydratase activity was detected in C. pasteurianum and Clostridium butyricum (48). All genes for the synthesis of coenzyme B 12 , the cofactor of glycerol dehydratase, can be found in the genome of C. kluyveri.…”
Section: Ethanol Dehydrogenases and Acetaldehyde Dehydrogenases In Amentioning
confidence: 99%
“…14,15,23) A comparison of the amino acid sequences of the corresponding subunits between diol and glycerol dehydratases 20,[23][24][25][26][27] showed high identities between them, except that the N-terminal 32 and 37 amino acid residues of the and subunits, respectively, of diol dehydratase are lacking in the corresponding subunits of glycerol dehydratase. Hence it was suggested that these regions might determine the solubility of these enzymes, although the hydropathy plots of diol dehydratase do not show any prominent hydrophobic peaks in these missing regions.…”
mentioning
confidence: 99%